Getting the Message of Abraham Ortelius’ Heart-Shaped Map and Atlas - Stephanie Inverso (Journal of Early Modern Studies)
In 1564, the celebrated Flemish cartographer Abraham Ortelius published his first cartographic work: a world map in the shape of a heart. This map manifests a spiritual call toward world unity heavily influenced by the heterodox sect known as the Family of Love. Six years later, Ortelius published the first edition of his groundbreaking magnum opus, an atlas entitled Theatrum orbis terrarum. With this later work, the unorthodox message of his cordiform map was not erased but transmuted into the form of an atlas. Abraham Ortelius’ example demonstrates how the ways in which knowledge circulated within humanist networks ensured that spiritual concerns, particularly unorthodox ones, continued to influence European cartography long after the rediscovery and translation of Ptolemy in the early fifteenth century.